Polysaccharide based Nano-Biocarrier in Drug Delivery - Giri, Tapan Kumar; Ghosh, Bijaya; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book discusses various fundamental aspects of polysaccharide based nano-biocarrier drug delivery systems and its application in the delivery of small molecules, proteins, peptides, oligonucleotides and genes. It also discusses advances in drug delivery systems in treatment of cancer, cardiovascular, pulmonary, and infectious diseases.
Chapter 1 Oral Delivery of Proteins and Polypeptides through Polysaccharide Nanocarriers----Hemant Ramchandra Badwaik, Kartik Nakhate, Leena Kumari, -- and Kalyani Sakure -- Chapter 2 --Oral Absorption of Polysaccharide Nanoparticles Loaded with -- Drug Molecule across the GIT----Tapan Kumar Giri -- Chapter 3 --Cellulose-Based Nanocomposites for Pharmaceutical and Biomedical -- Applications----Manuel Palencia, Mara E. Berrio, Angelica Garca-Quintero, -- and Tulio A. Lerma -- Chapter 4 --Recent Advances of Chitosan Nanoparticles as a Carrier for Delivery -- of Antimicrobial Drugs----Bijaya Ghosh and Tapan Kumar Giri -- Chapter 5 --Heparin and Its Derivatives-Based Nanoparticles for Cancer Therapy----Amit Kundu, Prasanta Dey, Arnab De, Subham Banerjee, Pradipta Sarkar, -- Amit Maity, and Hyung Sik Kim -- Chapter 6 --Delivery of Biomolecules to the Central Nervous System Using -- a Polysaccharide Nanocomposite----Anroop B. Nair, Shah Jigar, Chavda Vishal, Shah Hiral, and Patel Snehal -- Chapter 7 --Polysaccharide-Based Nanoparticles for the Enhanced Delivery of Poorly -- Soluble Drugs----Prithviraj Chakraborty, Urmi Chaurasia, Debarupa Dutta Chakraborty, -- and Indranil Chanda -- Chapter 8 --Development of Nanoparticles from Grafted Natural Polysaccharides -- for Drug Delivery----Anupam Roy, Sreyajit Saha, and Animesh Ghosh -- Chapter 9 --Environmental Responsive Polysaccharide Nanocarriers for -- Controlled Drug Delivery----Yamini S. Bobde and Balaram Ghosh -- Chapter 10 --Advancement of Biodegradable Polysaccharide Nanocarriers -- for Delivery of Herbal Extracts and Bio-Actives----K. Pallavi and G. H. Chethan -- Chapter 11 --Use of Polysaccharide Nanocarrier Systems for the Delivery -- of Curcumin and Its Derivative----K. Narayanan and Kiran S. Avadhani -- Chapter 12 --Polysaccharide-Based Nanocarriers for Drug Delivery -- into and through the Skin----Hemant Ramchandra Badwaik -- Chapter 13 --Polysaccharide Nanoparticle-Based Drug Delivery Approaches for Efficient -- Therapy of Diabetes----Vaswati Rita Das, Dibyendu Dutta, and Srijita Halder -- Chapter 14 --Chitosan-Based Nanoparticulate System for Pulmonary Drug Delivery----Tapan Kumar Giri, Bijaya Ghosh, and Falguni Patra -- Chapter 15 --Polysaccharide-Based Nanoparticles for Colon-Specific Drug Delivery----Moumita Das, Arindam Maity, Debanjana Chakraborty, -- and Lakshmi Kanta Ghosh -- Chapter 16 --Passive and Active Tumor Targeting of Polysaccharide Nanocarriers -- for Cancer Therapy----Miltu Kumar Ghosh and Falguni Patra -- Chapter 17 --Polysaccharide-Based Nanocarriers Loaded with Drugs for -- the Management of Obesity----Sandipan Dasgupta, Souvik Roy, Tania Chakraborty, and Nilanjan Sarkar.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Pharmacy; Cellulose based nanocomposite; Chitosan based nanoparticulate system; Environmental responsive polysaccharide nanocarrier; Oral delivery; Polysaccharide based nanoparticles; Polysaccharide nanocarrier for cancer therapy; Drug delivery systems; Polysaccharides -- Therapeutic use; Nanostructures -- Therapeutic use; Electronic books